State Clean Indoor Air Laws and smoking among adults with poor mental health. Issue 4 (December 2016) - Larson, Anne; Bovbjerg, Victor; Luck, Jeff
Abstract Persons with mental illness smoke at twice the rate of the general United States (US) population and die an average of 25-years younger, often from preventable diseases. This study seeks to determine whether disparities in smoking have increased over the past decade and whether Clean Indoor Air Laws (CIALs) are associated with changes in smoking among those with poor mental health. We used a fixed-effects model for estimation. CIALs were associated with 15 per cent decreased odds of smoking among adults in the US. Among those with poor mental health, these same laws had no effect. Between 2000 and 2010, the disparity in smoking rates between these two populations has steadily increased from 1.8 to 2.2 times greater. Given the lack of association between tobacco laws and smoking among those with poor mental health, alternative and more targeted tobacco reduction efforts may be necessary.